BIOMODEL OF ARTERIAL HYPERTENSION IN WISTAR RATS ADMINISTERED WITH SALINE SOLUTION TO 10% - Valido Díaz, Arianna (2018)
It is well-known that systemic arterial hypertension is one of the pathologies more prevalent in developed and developingsocieties. Th e use of experimental animal models has provided valuable information on many aspects of arterialhypertension including its etiology, physiopathology, complications and treatment. Because the etiology of arterialhypertension is heterogeneous, many of the experimental models with animals have been developed to imitate thediff erent facets of human arterial hypertension. In the past, most studies in experimental hypertension were performedon dogs; currently, in addition to the rat, chosen as the preferred animal species, other species, such as mice and rabbits,are also used in research protocols In the Experimental Toxicology Unit, there are numerous animal biomodels, butthere is no biomodel of arterial hypertension, so its creation would be of vital importance so that new natural productsand therapies can be tried to combat this disease that aff ects the world. Th erefore, the objective of our project was todescribe the existing biomodels of arterial hypertension in Wistar rats with the purpose of testing natural products withhypotension eff ects. Th ere was an increase in body weight of rats administered 10% saline compared to control rats.Blood pressure values at the second week showed signifi cant diff erences with respect to the control group. At the end of the third week, mean blood pressure in the administered group was SBP (systolic blood pressure) -152.0 mmHg andDBP (diastolic blood pressure) -110.0 mmHg, indicating hypertensive rats.